DAMPAK PEMBINAAN AKHLAK TERHADAP SELF CONTROL REMAJA - Hafifah, Wafiq; Hamdanah, Hamdanah; Surawan, Surawan (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract: The teenage phase is a process of searching for one's identity or identity, but the fact is that not all teenagers are able to exercise good self-control. One of the efforts made for teenagers to be able to control themselves is through moral development. The aim of this research is to analyze the impact of moral development on self-control in adolescents. This research uses a qualitative approach regarding the impact of moral development on adolescents in controlling themselves. The aim of this research refers to the impact of moral development on adolescent self-control. The results of the research show that there is a positive impact of moral development on adolescent self-control, namely changes in thought patterns and thought patterns, changes in principles, changes in behavior. Meanwhile, the positive impact on other people is the impact on family and society. Keywords: Moral Development, Self Control, Youth Abstrak: Fase remaja merupakan proses pencarian jati diri atau identitas diri, namun faktanya tidak semua remaja mampu melakukan pengendalian diri dengan baik. Salah satu upaya yang dilakukan pada remaja agar mampu mengendalikan diri adalah melalui pembinaan akhlak. Tujuan penelitian ini adalah untuk menganalisis dampak pembinaan akhlak terhadap self-control pada remaja. Penelitian ini menggunakan pendekatan kualitatif mengenai dampak perkembangan moral pada remaja dalam mengendalikan diri. Tujuan penelitian ini mengacu pada dampak perkembangan moral terhadap pengendalian diri remaja. Hasil penelitian menunjukkan adanya dampak positif dari adanya perkembangan moral terhadap pengendalian diri remaja yaitu perubahan pola pikir dan pola pikir, perubahan prinsip, perubahan perilaku. Sedangkan dampak positifnya bagi orang lain adalah dampaknya terhadap keluarga dan masyarakat. Kata Kunci: Pembinaan Akhlak, Self Control, Remaja